Postoperative visual loss following dorsal root entry zone rhizotomy: A dreaded complication after a benign procedure - R K Mishra; C Mahajan; A Bindra; K Goyal (Saudi Journal of Anaesthesia, 2016)
Postoperative visual loss (POVL) is a rare but grave postoperative complication. It has been mainly reported in patients undergoing cardiac and spinal surgeries. Dorsal root entry zone (DREZ) is pain relieving procedure performed in patients with refractory neuropathic pain with minimal complication rate. We present a case of unilateral POVL following DREZ rhizotomy in prone position in a patient having brachial plexus neuropathy. Exact etiology of vision loss was though not clear; hypotension, use of vasopressors and hemodilution may have led to vision loss in this patient. This case report highlights the associated risk factors for development of this hazardous complication.